Sustainability Assessment at the 21st century - José Bastante-Ceca, María; Luis Fuentes-Bargues, Jose; Hufnagel, Levente; Mihai, Florin-Constantin; Iatu, Corneliu (IntechOpen, 2020)
The sustainability of the human society is endangered by the global human-ecological crisis, which consists of many global problems that are closely related to each other. In this phenomenon, the global population explosion has a central role, because more people have a larger ecological footprint, a larger consumption, more intensive pollution, and a larger emission of carbon dioxide through their activities.This book presents the current state of sustainability and intends to provide the reader with a critical perspective of how the 21st century societies must change their development model facing the new challenges (internet of things, industry 4.0, smart cities, circular economy, sustainable agriculture, etc.), in order to achieve a more liveable world.